EPIZOOTIOLOGY OF ELAPHOSTRONGYLUS ALCES IN SWEDISH MOOSE - Stéen, Margareta; Olsson Ressner, Ing-Marie; Olsson, Bodil; Petersson, Erik (Lakehead University, 2016)
A total of 961 harvested and 241 unharvested moose (Alces alces) carcasses and parts from throughout Sweden were examined for Elaphostrongylus alces from 1985 to 1989. When available, the central nervous system and skeletal muscles were searched for adult nematodes, and lungs and feces were examined for first-stage larvae. The parasite was distributed throughout Sweden with highest prevalence (56%) in the central region and lowest in the south (13%). Prevalence was highest in calves and old moose (>9 years) and lowest in middle-aged animals (5–9 years), with no statistical difference between sexes, although prevalence trended higher in young males. Body condition and abundance of Elaphostrongylus alces were negatively correlated, and condition was poorer in unharvested than harvested moose. A short (39–73 days) prepatent period was documented, and calves as young as 1.5 months were infected. These results indicate the importance of continued surveillance of Elaphostrongylus alces, particularly because a warming climate will likely increase abundance of intermediate mollusk hosts and possibly cause increased infection of moose.